EFFORTS TO STOP BULLYING IN SCHOOLS: STRATEGIES, CHALLENGES AND SOLUTIONS - Irianto, Bambang Sugeng; Sutrisno, Sutrisno; Suryasaputra, Ruswiati (EQUALEGUM International Law Journal, 2024)
Background. School bullying has become a serious issue that affects the mental and emotional well-being of students around the world. This research discusses efforts to overcome bullying in the school environment, including prevention strategies, challenges faced, and solutions that can be implemented. Research Method. The method used in this research was a literature review by observing primary resource material as well as literature from journals, books, and best practices to provide insight into effective approaches to stop bullying in schools. Findings. Bullying in Indonesia significantly impacts students' academic achievement, social life, mental and physical health, and lives. To prevent bullying, schools, families, and the community must take action, including early detection, outreach, support, strict regulations, role modeling, teaching, and helping perpetrators stop bad behavior. Schools should be sensitive to students' situations, socialize through anti-bullying posters, provide support to victims, and implement strict regulations. Victims may experience depression, anxiety disorders, changes in sleep and eating patterns, health problems, and decreased academic performance. Conclusion. Bullying in schools is a significant issue that requires collective action from the educational community. Effective prevention strategies, addressing challenges, and creating safe environments can help end bullying and protect student well-being. Factors like lack of knowledge, environmental influence, and teacher bullying contribute to the problem. Schools' role in addressing bullying is not optimal, and victims need further intervention.